Elena Cotta Ramusino, Elizabeth Bowen’s Other Writing. A Study of Her Non-Fictional Prose (Altre Modernità, 2018)
Elena Cotta Ramusino, Elizabeth Bowen’s Other Writing. A Study of Her Non-Fictional Prose(Como and Pavia, Ibis, 2018, 123 pp. ISBN 978-88-7164-579-7)by Elena Ogliari